Level and transport pattern of faecal coliform bacteria from tropical urban catchments - Mohd Ekhwan, Toriman; M.F., Chow; Z, Yusop (2013)
Urbanization and frequent storms play important roles in increasing faecal bacteria pollution, especially for tropical urban catchments. However, only little information on the faecal bacteria levels from different land use types and the factors that influence bacteria concentrations is available. Thus, the objectives of this study were to quantify the levels and transport mechanism of faecal coliforms (FCs) from residential and commercial catchments. Stormwaters were sampled and the runoff flow rates were measured from both catchments during four storm events in Skudai, Malaysia. The samples were then analysed for FC, biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solids (TSS) and ammoniacal-nitrogen (NH3-N) concentrations. Intra-storm and inter-storm characteristics of FC bacteria were investigated in order to identify the level and transport pattern of FC. The commercial catchment showed significantly higher event mean concentration (EMC) of FC than the residential catchment. For the residential catchment, the highest bacterial concentrations occurred during the early part of stormwater runoff with peak concentrations usually preceding the peak flow. First flush effect was more prevalent at the residential catchment.